PENINGKATAN KESADARAN MASYARAKAT TENTANG GAYA HIDUP SEHAT UNTUK MENCEGAH DIABETES MELLITUS - Lestari, Tutik; Yusnita, Yusnita; Andiani, Andiani; Sumarto, Sabaria; Aldjokdja, Retno Kartika; Hasan, Risma Hi; Laego, Riyanti; Daud, Ruslia; Manteto, Tiara; Diman, Tiara; Aulia, Rifanda; Salim, Nurmai; Minggu, Musdalifa; Sahsun, Darmila; Langasa, Siti AIgina; Bada, Wahdi; M, Fitra Tunisyah; Fadilah, Fadilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diabetes mellitus is a non-communicable disease whose prevalence continues to increase globally, primarily due to unhealthy lifestyles. A healthy lifestyle, which includes a balanced diet, regular physical activity, stress management, and adequate sleep, plays a crucial role in preventing diabetes mellitus. This community service programme aims to increase public understanding of the importance of a healthy lifestyle as a preventative measure for diabetes mellitus. The activity, conducted in Tosa Village, targeted women from the Family Welfare Movement (PKK) through lectures, discussions, and Q&A sessions. The results showed an increase in the average pre- and post-test scores, from 5.39 to 12.79. It is hoped that this health education programme will help the community change unhealthy behaviors to adopt healthy ones in their daily lives to avoid diabetes mellitus and other diseases.